Implications of The Minimum Competency Assessment (AKM) on The Literature Motivation Of Students Of SMP PGRI 2 Wates, Blitar Regency - Muhammad Aditya Wisnu Wardana; Sumarwati Sumarwati; Budhi Setiawan (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2022)
The application of AKM or Minimum Competency Assessment is used to measure students' abilities, one of which is in terms of literacy, which is oriented towards technology-based learning, innovation, and critical reasoning. In the aspect of literacy in the implementation of AKM, it has a contextual nature and is able to solve problems (problem solving) in providing stimulation for students to think critically or critical thinking. The study used a questionnaire quantitative research method presented on a Likert scale with five answer choices, namely strongly agree (SS); agree (S); normal (BS); disagree (TS); strongly disagree (STS). The measuring tool used in reading motivation is the Reading Motivation Questionnaire (RMQ) developed by the author into 7 dimensions, including (a) curiosity, (b) involvement, (c) academic value, (d) competition, (e) recognition. social, (f) regulation of emotions, and (g) freedom from boredom. To measure literacy motivation in junior high school students as the effect of implementing AKM on students. The source of this research is class VIII students at SMP PGRI 2 Wates who follow the AKM as the target school in the Class 4 Teaching Campus activities in 2022. The results obtained based on the measuring instrument for students' literacy motivation after carrying out the assessment on students concluded an increase in literacy motivation. students after implementing AKM on students. Keywords: literacy motivation; Minimum Competency Assessment; Reading Motivation Questionnaire